Frontline and Factory: Comparative Perspectives on the Chemical Industry at War, 1914-1924 - Macleod, Roy.; Johnson, Jeffrey Allan; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
The First World War is often called the 'chemists' war'. But few realise precisely how, or the extent to which modern chemistry became a significant factor in the struggle, and would be in turn deeply shaped by it. Gathering momentum at first, by 1916, success in applying scientific knowledge to 'frontline and factory' became a measure of a nation's capacity to win an industrial war. In the end, the titanic contest was won in large part through the command of raw materials and industrial output. This book represents a first considered attempt to study the factors that conditioned industrial chemistry for war in1914-18. Taking a comparative perspective, it reflects on the experience of France, Germany, Austria, Russia, Britain, Italy and Russia, and points to significant similarities and differences. It looks at changing patterns in the organisation of industry, and at the emerging symbiosis between science, industry and the military, which contributed to the first 'academic-military-industrial' complex of the 20th century. At the same time, it reflects on the world's first, and ultimately unsuccessful attempt to monitor 'dual-use' chemical technologies, and so restrict the proliferation of an important category of weapons of mass destruction.
Technological Mobilization and Munitions Production: Comparative Perspectives on Germany and Austria -- Mobilization and Industrial Policy: Chemicals and Pharmaceuticals In The French War Effort -- First World War Explosives Manufacture: The British Experience -- Transforming a Village into an Industrial Town: The Royal Prussian Powder Plant in Kirchmöser (Brandenburg) -- Wartime Chemistry in Italy: Industry, the Military, and the Professors -- Munitions, the Military, and Chemistry in Russia -- Technical Expertise and U.S. Mobilization, 1917-18: High Explosives and War Gases -- Operating on Several Fronts: The Trans-National Activities of Royal Dutch/Shell, 1914-1918 -- Kuhlmann at War, 1914-1924 -- Organizing for Total War: DuPont and Smokeless Powder in World War I -- Science and the Military: The Kaiser Wilhelm Foundation for Military-Technical Science -- Managing Chemical Expertise: The Laboratories of the French Artillery and the Service des Poudres -- The War the Victors Lost: The Dilemmas of Chemical Disarmament, 1919-1926.
Keywords: SCIENCE (GENERAL).; SCIENCE -- HISTORY; CHEMICAL ENGINEERING; HISTORY; ECONOMICS; BUSINESS LOGISTICS; SCIENCE; HISTORY OF SCIENCE; INDUSTRIAL CHEMISTRY/CHEMICAL ENGINEERING; HISTORY; ECONOMIC SYSTEMS; PRODUCTION/LOGISTICS.